Development of SPACE‐II for rapid sample exchange at SPring‐8 macromolecular crystallography beamlines. Issue 2 (10th February 2020) - Murakami, Hironori; Hasegawa, Kazuya; Ueno, Go; Yagi, Naoto; Yamamoto, Masaki; Kumasaka, Takashi
Abstract : A rapid and reliable sample changer, SPACE‐II, has been developed at the SPring‐8 macromolecular crystallography beamline BL41XU. It enables samples to be exchanged in 16 s, of which its action accounts for only 11 s. Two years of operating SPACE‐II demonstrated that the average number of sample exchanges per day was increased by 40% compared with the previous model, and it had an error rate of only 0.089%. Abstract : Reducing the sample‐exchange time is a crucial issue in maximizing the throughput of macromolecular crystallography (MX) beamlines because the diffraction data collection itself is completed within a minute in the era of pixel‐array detectors. To this end, an upgraded sample changer, SPACE‐II, has been developed on the basis of the previous model, SPACE (SPring‐8 Precise Automatic Cryo‐sample Exchanger), at the BL41XU beamline at SPring‐8. SPACE‐II achieves one sample‐exchange step within 16 s, of which its action accounts for only 11 s, because of three features: (i) the implementation of twin arms that enable samples to be exchanged in one cycle of mount‐arm action, (ii) the implementation of long‐stroke mount arms that allow samples to be exchanged without withdrawal of the detector and (iii) the use of a fast‐moving translation and rotation stage for the mount arms. By pre‐holding the next sample prior to the sample‐exchange sequence, the time was further decreased to 11 s in the case of automatic data collection, of which the action of SPACE‐II accounted for 8 s. Moreover, the sample capacity was expanded from four to eight Uni‐Pucks. The performance of SPACE‐II has been demonstrated in over two years of operation at BL41XU; the average number of samples mounted on the diffractometer in one day was increased from 132 to 185, with an error rate of 0.089%, which counted incidents in which users could not continue with an experiment without recovery work by entering the experimental hutch. On the basis of these results, SPACE‐II has been installed at three other MX beamlines at SPring‐8 as of July 2019. The fast and highly reliable SPACE‐II is now one of the most important pieces of infrastructure for the MX beamlines at SPring‐8, providing users with the opportunity to fully make use of limited beamtime with brilliant X‐rays.